Vers une couverture sanitaire universelle au Sénégal - Sameera Awawda; Bruno Ventelou; Mohammad Abu-Zaineh (Revue Internationale des Études du Développement)
This study aims to assess different funding scenarios for universal health coverage in Senegal. The microsimulation method used makes it possible to examine the impact of the funding methods for universal health coverage (UHC) on household consumption, as well as on public revenue and expenditure. The results show that the expansion of UHC to the whole population coupled with a reduction in the direct costs of care would increase households’ access to health services. The methodological approach proposed here allows calculating the financial cost associated with covering the entire population and healthcare services, and therefore assessing the feasibility of public policies aimed at promoting the implementation of UHC ex ante.